Microbial flora in Ukay-ukay clothing from flea markets in Valencia City, Bukidnon - Samaniego, Lorelei G. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2016)
Microflora from selected ukay-ukay clothing in Valencia City, Bukidnon were isolated and identified, and the effectiveness of commonly used antimicrobial agents against the microbial isolates was assessed through a standard antimicrobial disc diffusion assay. The effectiveness of conventional hand washing and sun drying in eradicating the microbes from ukay-ukay clothing was also assessed. Nine bacteria namely; Micrococcus luteus, Staphylococcus sp., Enterobacter agglomerans, E. aerogenes, E. hafniae, Citrobacter freundii, Salmonella arizonae, Serratia sp., Edwardsiella sp., and seven funfi; Aspergillus fumigatus, A. niger, A. nidulans, Penicillium glabrum, Rhizopus nigricans, Fusarium sp., Monila sp. were recovered and identified. One fungal species remained unidentified. Antimicrobial susceptibility tests showed that majority of the bacteria were susceptible to doxycycline, tetracycline and nonfloxacin. However, majority of the isolates were resistant to penicillin. Tioconazole was the most effective among the antifungal agents tested. Majority of the fungal isolates were resistant to sulfur+ZnO+salicylic acid, clotrimazole, benzoic acid+salicylic acid, ketocona-zole+clobetasol propionate and terbinafine hydrochloride. Reduction in colony counts after hand washing and sun drying reached 92.40% and 96.86% for bacteria and fungi, respectively. This study shows that ukay-ukay clothing harbor microbial pathogens with varying resistance/susceptibility to popular antimicrobial agents.